The Network Structure of Decision-Making Competence in Chinese Adults - Peng, Jiaxi; Ren, Lei; Yang, Nian; Zhao, Luming; Fang, Peng; Shao, Yongcong (Frontiers in Psychology, 2020)
Decision-making competence refers to the ability to make better decisions, as defined by decision-making principles posited by models of rational choice. The Adult Decision-Making Competence scale (A-DMC) is a relatively mature evaluation tool used for decision-making competence. However, the A-DMC is yet far from other mature psychological evaluation tools, and especially the structure of A-DMC remains unclear. In the current study, we estimated a regularized partial correlation network of decision-making competence for a Chinese sample consisting of 339 adults who were evaluated by the A-DMC, and then network analysis was used. The results revealed that all nodes of the decision-making competence networks are positively associated, except for the association of resistance to framing and resistance to sunk costs. The strongest edge was between resistance to framing and applying decision rules (regularized partial correlation=0.37). The centrality indicators of resistance to framing and applying decision rules were highest revealing that these two variables may play important roles in the decision-making competence network. Our study conceptualizes the decision-making competence from network perspectives, so as to provide some insights for future researches.